2015
DOI: 10.1159/000369212
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization and Antioxidant and Antiproliferative Activities of Different <b><i>Ganoderma </i></b>Collections

Abstract: The aim of this study was to conduct a molecular and biochemical characterization and to compare the antioxidant and antiproliferative activities of four Ganoderma isolates belonging to Ganoderma lucidum (Gl-4, Gl-5) and Ganoderma resinaceum (F-1, F-2) species. The molecular identification was performed by ITS and IGS sequence analyses and the biochemical characterization by enzymatic and proteomic approaches. The antioxidant activity of the ethanolic extracts was compared by three different methods and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 33 publications
(51 reference statements)
5
25
1
Order By: Relevance
“…Chemical antioxidant tests consistently revealed the free radical scavenging activity of G. lucidum. Twelve studies reported the scavenging activity of G. lucidum for different free radicals including 2,2-diphenylpicrylhydrazyl radical (DPPH ⋅ ), 2,2 ′ -azino-bis(3-ethylbenzthiazoline-6-sulphonic acid) radical (ABTS ⋅ +), hydroxyl radical (HO ⋅ ), and hydrogen peroxide radicals (H 2 O 2 ) [39][40][41][42][43][44][45][46][47][48][49] (Table 5). G. lucidum also inhibits lipid peroxidation [23,49].…”
Section: In Vitro Antioxidant Of G Lucidum and Its Possiblementioning
confidence: 99%
“…Chemical antioxidant tests consistently revealed the free radical scavenging activity of G. lucidum. Twelve studies reported the scavenging activity of G. lucidum for different free radicals including 2,2-diphenylpicrylhydrazyl radical (DPPH ⋅ ), 2,2 ′ -azino-bis(3-ethylbenzthiazoline-6-sulphonic acid) radical (ABTS ⋅ +), hydroxyl radical (HO ⋅ ), and hydrogen peroxide radicals (H 2 O 2 ) [39][40][41][42][43][44][45][46][47][48][49] (Table 5). G. lucidum also inhibits lipid peroxidation [23,49].…”
Section: In Vitro Antioxidant Of G Lucidum and Its Possiblementioning
confidence: 99%
“…G. lingzhi seems to have more triterpenic acids than G. lucidum s.str. [ 16 18 ]. The morphological characteristics of the species also differ [ 19 – 21 ].…”
Section: G Lucidum and G Frondosamentioning
confidence: 99%
“…Total phenol content in phenol extracts was ranged from 2.5 to 12.3 lg/g, and detected phenolic compounds in extracts were the p-hydroxybenzoic, pcoumaric and cinnamic acid. The flavonoids in the ethanolic extracts from mycelia of Ganoderma lucidum strains Gl-4 and Gl-5 were analyzed, and quercetin, myricetin, and morin were identified (Saltarelli et al 2015). Gallic acid (1103 lg/g) was the only detected phenolic compound in methanol extract of wild growing Ganoderma lucidum collected from Fruška gora, Serbia.…”
Section: Phenolic Compounds Analysesmentioning
confidence: 99%
“…Although G. lucidum represents poor source of phenolic compounds, some investigations reported that these compounds provide the greatest contribution to the antioxidant activity of its extracts (Ć ilardžić et al 2014;Saltarelli et al 2009). The major flavonoids with effective antioxidant activity in the ethanol extract from mycelia of G. lucidum are quercetin, myricetin, and morin (Saltarelli et al 2015).…”
Section: Introductionmentioning
confidence: 99%